THE IMPACT OF LIQUIDITY, LEVERAGE, AND PROFITABILITY ON MARKET VALUE THROUGH DIVIDEND POLICY: EMPIRICAL EVIDENCE FROM THE INDONESIA STOCK EXCHANGE (2021–2024) - Livia Pinkan Imara; Darsono Darsono (Diponegoro Journal of Accounting, 2026)
This study is motivated by the inconsistency between internal financial performance and market valuation among firms listed on the Indonesia Stock Exchange, where financial indicators are not always interpreted uniformly by investors. The analysis aims to examine how liquidity, leverage, and profitability influence dividend policy and how these factors ultimately affect firm market value.A quantitative approach is applied using purposive sampling, resulting in 232 firm-year observations with consistent financial data during the 2021–2024 period. Liquidity, leverage, and profitability function as independent variables, dividend policy operates as a mediating variable, and market value is treated as the dependent variable. The relationships among variables are tested using multiple linear regression and path analysis to capture both direct and indirect effects.The findings reveal that profitability has a significant negative effect on dividend policy, indicating that firms with higher earnings tend to retain profits rather than distribute them. Profitability also demonstrates a significant positive influence on market value, suggesting that investors prioritize earning capacity as a key indicator of firm strength. Liquidity and leverage do not show significant effects on dividend policy. Dividend policy does not significantly affect market value and does not serve as a mediating variable. These results suggest that investors respond more strongly to fundamental financial performance than to dividend-related signals in evaluating firm value.